PENGARUH PENGGUNAAN METODE PEMBELAJARAN MIND MAPPING TERHADAP PENINGKATAN PEMAHAMAN MATERI EKONOMI SISWA - Karmila; Syamsuria; Emmi Azis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Effect of Using Mind Mapping Learning Methods on Improving Students' Understanding of Economic Material. Thesis, Economic Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Bone, Academic Year 2025. Supervised by Advisor I, Mrs. Syamsuria, S.Pd., M.Pd., and Advisor II, Mrs. Emmi Azis, S.Pd., M.Pd. This research aims to determine the effect of using the mind mapping learning method on improving students' understanding of economic material. The population in this study consisted of all Grade VII students at SMP Negeri 5 Lappariaja in the 2024/2025 academic year. The sampling technique used was full sampling, whereby all Grade VII students were included as research samples. This study employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. The use of the mind mapping method was proven to influence the improvement of students' understanding of economic material. This is evidenced by the results of the Paired Sample t-Test analysis, where the average posttest score (73.50) was higher than the average pretest score (55.00), with a significance value of 0.000 < 0.05. This indicates a significant difference before and after treatment with the mind mapping learning method. Simple linear regression analysis results showed a positive and significant influence between the use of the mind mapping method and student understanding. An R Square value of 0.510 indicates that 51% of the variation in student understanding is influenced by the implementation of the mind mapping method. The significance value of 0.000 < 0.05 reinforces that the relationship is statistically significant. In conclusion, the mind mapping learning method provides a real influence on improving students' understanding of economic material, based on both test results and student perceptions through questionnaires.